1995
DOI: 10.1557/jmr.1995.1327
|View full text |Cite
|
Sign up to set email alerts
|

Coating of uniform inorganic particles with polymers: III. Polypyrrole on different metal oxides

Abstract: Five kinds of uniform metal oxide particles (α-Fe2O3, CeO2, CuO, NiO, and SiO2) were coated with polypyrrole by reacting the dispersed solids with pyrrole in a water/ethanol medium without the use of a soluble oxidant. When the process was carried out in air, all particles were coated with the polymer, although the thickness of the layer varied on different cores. In CuO dispersions, independent polypyrrole particles were produced in addition to coated spheres. While oxygen is the major oxidant that initiates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…This approach was employed to obtain poly(pyrrole) coatings on a range of inorganic cores by using the active sites on the metal oxide surfaces to initiate the polymerization of pyrrole. [26,27] Hematite (a-Fe 2 O 3 ), silica-modified hematite, and cerium(IV) oxide (CeO 2 ) were coated with poly(pyrrole) by exposing the inorganic cores to the polymerization medium of pyrrole in an ethanol/water mixture and heating to 100 C. The poly(pyrrole)-coated a-Fe 2 O 3 and CeO 2 particles were found to be electrically conductive. [26] In a subsequent study, it was shown that CeO 2 and copper(II) oxide (CuO) react with the adsorbed pyrrole molecules through a reductive-dissolution process that involves oxidation of the monomers and release of the metal ions, whilst a-Fe 2 O 3 and silica (SiO 2 ) were found to be inactive in the polymerization.…”
Section: Surface Modification Via Polymerization Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach was employed to obtain poly(pyrrole) coatings on a range of inorganic cores by using the active sites on the metal oxide surfaces to initiate the polymerization of pyrrole. [26,27] Hematite (a-Fe 2 O 3 ), silica-modified hematite, and cerium(IV) oxide (CeO 2 ) were coated with poly(pyrrole) by exposing the inorganic cores to the polymerization medium of pyrrole in an ethanol/water mixture and heating to 100 C. The poly(pyrrole)-coated a-Fe 2 O 3 and CeO 2 particles were found to be electrically conductive. [26] In a subsequent study, it was shown that CeO 2 and copper(II) oxide (CuO) react with the adsorbed pyrrole molecules through a reductive-dissolution process that involves oxidation of the monomers and release of the metal ions, whilst a-Fe 2 O 3 and silica (SiO 2 ) were found to be inactive in the polymerization.…”
Section: Surface Modification Via Polymerization Processesmentioning
confidence: 99%
“…[26] In a subsequent study, it was shown that CeO 2 and copper(II) oxide (CuO) react with the adsorbed pyrrole molecules through a reductive-dissolution process that involves oxidation of the monomers and release of the metal ions, whilst a-Fe 2 O 3 and silica (SiO 2 ) were found to be inactive in the polymerization. [27] Uniform poly(pyrrole) coatings surrounding the core can be obtained using this approach, as displayed in Figure 1 for poly(pyrrole)-coated SiO 2 particles. [27] It was further shown that the thickness of the polymer coating can be controlled by varying the contact time of the cores with the polymerization solution and that the polymer layer thickness is dependent on the type of core used and the presence of additional polymer (e.g., polyvinyl alcohol).…”
Section: Surface Modification Via Polymerization Processesmentioning
confidence: 99%
“…However, the higher energy of the quinoid section between them binds them together resulting in correlated motion. The net effect is the formation of a doubly charged defect acting like a single entity and delocalized over several rings (3)(4)(5) i.e., a bipolaron. The formation of bipolarons implies a net free energy gain in forming a closed shell defect from two open shell structures.…”
Section: Mechanism Of Conductivitymentioning
confidence: 99%
“…Depending on the nature of the components used and the method of preparation, significant differences in composite properties may be obtained. Nanocomposites of conducting polymers have been prepared by various methods such as colloidal dispersions [2], electrochemical encapsulation [3], coating of inorganic polymers, and insitu polymerization with nanoparticles [4] and have opened new avenues for material synthesis. The combination of the magnetic nanoparticles with conducting polymer leads to formation of ferromagnetic conducting polymer composite possessing unique combination of both electrical and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The agglomeration in these magnetic nanoparticles due to Vander Waal's and magneto static interparticle interaction hampers their use for technological applications. Several methods have been employed to reduce this problem of agglomeration, namely, blending colloidal nanomagnetic particles with polymers, coating of oxide particles with polymers like PVA, PVP,PMA etc., forming a core shell structure or embedding the particles in a polymer matrix [6][7][8][9]. These so called nanocomposites are also used in blend with conducting polymers like polypyrrole (PPY), polyaniline (PANI) etc.…”
Section: Introductionmentioning
confidence: 99%